2010
DOI: 10.1055/s-0029-1240899
|View full text |Cite
|
Sign up to set email alerts
|

5,6,3′,4′-Tetrahydroxy-7-methoxyflavone as a Novel Potential Proteasome Inhibitor

Abstract: Proteasome inhibition is one of the new pharmaceutical approaches to study antitumor activity. Although the active components are not yet identified for either treating or preventing cancer, the low toxicity plant Anisomeles ovata R. Br. has been used in traditional herbal medicine for more than 1000 years. In this study, the methanol extract from Anisomeles ovata showed potent inhibition of proteasome activity. Twenty compounds, two macrocycylic diterpenoids, six aromatics, seven flavonoids, and five phenylet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The 5-TDMF used in this study was purified as a yellow power from the methanol-fraction of Anisomeles ovata by our team following the published procedure [14]. The purified 5-TDMF exhibited similar spectroscopic data (IR, NMR, MS) to a previous publication [31].…”
Section: Isolation Of 5-tdmf From the Whole Plant Of Anisomeles Ovatamentioning
confidence: 81%
See 1 more Smart Citation
“…The 5-TDMF used in this study was purified as a yellow power from the methanol-fraction of Anisomeles ovata by our team following the published procedure [14]. The purified 5-TDMF exhibited similar spectroscopic data (IR, NMR, MS) to a previous publication [31].…”
Section: Isolation Of 5-tdmf From the Whole Plant Of Anisomeles Ovatamentioning
confidence: 81%
“…In order to identify the active ingredients of Anisomeles ovata, a number of chemical components have been identified, including flavonoids, terpenoids and steroids [9,[11][12][13]. Among the isolated compounds, 5,6,4′-trihydroxy-7,3′-dimethoxyflavone (5-TDMF) was found to be the major flavonoid in the methanol extract of Anisomeles ovata [14]. However, a detailed pharmacological study of 5-TDMF has yet to be reported.…”
Section: -Tdmf Possesses Weak or No Cytotoxicity Toward The Experimementioning
confidence: 99%